Characterization of the Angiogenic Potential of Human Regulatory Macrophages (Mreg) after Ischemia/Reperfusion Injury In Vitro. (25th June 2019) - Hummitzsch, Lars; Zitta, Karina; Rusch, Rene; Cremer, Jochen; Steinfath, Markus; Gross, Justus; Fandrich, Fred; Berndt, Rouven; Albrecht, Martin
Abstract : Ischemia/reperfusion- (I/R-) induced organ damage represents one of the main causes of death worldwide, and new strategies to reduce I/R injury are urgently needed. We have shown that programmable cells of monocytic origin (PCMO) respond to I/R with the release of angiogenic mediators and that transplantation of PCMO results in increased neovascularization. Human regulatory macrophages (Mreg), which are also of monocytic origin, have been successfully employed in clinical transplantation studies due to their immunomodulatory properties. Here, we investigated whether Mreg also possess angiogenic potential in vitro and could represent a treatment option for I/R-associated illnesses. Mreg were differentiated using peripheral blood monocytes from different donors (N = 14 ) by incubation with M-CSF and human AB serum and stimulation with INF-gamma. Mreg cultures were subjected to 3 h of hypoxia and 24 h of reoxygenation (resembling I/R) or the respective nonischemic control. Cellular resilience, expression of pluripotency markers, secretion of angiogenic proteins, and influence on endothelial tube formation as a surrogate marker for angiogenesis were investigated. Mreg showed resilience against I/R that did not lead to increased cell damage. Mreg express DHRS9 as well as IDO and display a moderate to low expression pattern of several pluripotency genes (e.g., NANOG, OCT-4, and SOX2). I/R resulted in an upregulation of IDO (p < 0.001 ) while C-MYC and KLF4 were downregulated (p < 0.001 andp < 0.05 ). Proteome profiling revealed the secretion of numerous angiogenic proteins by Mreg of which several were strongly upregulated by I/R (e.g., MIP-1alpha, 19.9-fold; GM-CSF, 19.2-fold; PTX3, 5.8-fold; IL-1 β, 5.2-fold; and MCP-1, 4.7-fold). The angiogenic potential of supernatants from Mreg subjected to I/R remains inconclusive. While Mreg supernatants from 3 donors induced tube formation, 2 supernatants were not effective. We suggest that Mreg may prove beneficial as a cell therapy-based treatment option for I/R-associated illnesses. However, donor characteristics seem to crucially influence the effectiveness of Mreg treatment.